2015
DOI: 10.3109/07434618.2015.1052887
|View full text |Cite
|
Sign up to set email alerts
|

“Social Media has Opened a World of ‘Open communication:’” experiences of Adults with Cerebral Palsy who use Augmentative and Alternative Communication and Social Media

Abstract: An online focus group was used to investigate the experiences of nine individuals with cerebral palsy who use augmentative and alternative communication (AAC) and social media. Information was gathered related to (a) advantages of social media, (b) disadvantages of social media, (c) barriers to successful use, (d) supports to successful use, and (e) recommendations for other individuals using AAC, support personnel, policy makers, and technology developers. Participants primarily chose to focus on social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 29 publications
2
30
0
9
Order By: Relevance
“…Apart from this protective function, a recent US study that focussed on social media showed similar results to the findings of the current study when the authors described the benefits for persons who use AAC as connecting them with other individuals, making them feel typical, making communication easier, gaining independence and getting help (Caron & Light 2015). They also found potential employment benefits.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Apart from this protective function, a recent US study that focussed on social media showed similar results to the findings of the current study when the authors described the benefits for persons who use AAC as connecting them with other individuals, making them feel typical, making communication easier, gaining independence and getting help (Caron & Light 2015). They also found potential employment benefits.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, these mainstream mobile technologies can also serve the functions of specialized AAC technologies – this is another important and positive implication of the findings of the study, since these mainstream technologies are comparatively more powerful, compact, and have a longer battery life, which is essential for communicating without worrying to stop and recharge a device, as is often the case with specialized AAC devices (Alper & Haller 2015. Additionally, as Caron and Light (2015) and Light and McNaughton (2014) suggest, social media via networked mobile technologies give individuals with significant communication disabilities opportunities to ‘increase, maintain, or improve’ their own communication in everyday contexts, be they synchronous or asynchronous conversations, face-to-face or from a distance, and among others with or without disabilities. Recent research has already demonstrated the benefits of the use of social media by individuals with severe communication disabilities in the United States (Caron & Light 2015).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations